Diversity of Reef Fish in Pancuran Beach and The Harbor Area of Karimunjawa National Park - Dhanis Nuranggitasari; Ardyan Pramudya Kurniawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Research on the biodiversity of Ikhthiofauna in coral reef ecosystems in Karimunjawa National Park was carried out in March 2021. This study aimed to study the species of reef fish found in the National Park Karimunjawan, to study the dominant reef fish species, the level of diversity, and the factors that influence reef fish biodiversity in Karimunjawa National Park. Data collection was carried out at two research locations, namely Pancuran Beach and Harbor Pier. This research was conducted using the visual census method at each station made transects with a distance of 5 m per transect. Each transect is 50 m long parallel to the shoreline. Observations were made by snorkeling along the 2.5 m transect line to the right and the left, then the fish obtained were drawn using waterproof paper, numbered per species, and photographed using an underwater camera for identification. Data analysis was carried out, including descriptive analysis to analyze fish characteristics and quantitative analysis to calculate data, including the Shannon Diversity Index (H'), Simpson's Dominance Index (C), and Evenness Index (E). The environmental parameters taken include water temperature, salinity, pH, and DO. This study identified a total of 59 species of reef fish from 17 families, with the dominant family was Pomacentridae. The level of diversity (H') at the research location at Pancuran Beach reachedÃÂ 3.392, while at the Harbor Pier, it reached 3.428. The Simpson Dominance Index (C) value at the Pancuran Beach location is 0.044, and the Harbor Pier is 0.047. The Evenness Index (E) value at the Pancuran Beach location is 0.88, and the Harbor Pier is 0.85. The difference in the index value is influenced by various environmental factors, both physically, chemically, and biologically.ÃÂ